2022
DOI: 10.3389/fpubh.2022.999272
|View full text |Cite
|
Sign up to set email alerts
|

Experiences pertaining to child nutrition and care provision among early care and education stakeholders, sponsors, and center directors during the COVID-19 pandemic: A multi-method study

Abstract: PurposeThis study used multiple methods (interviews, survey) to assess experiences of stakeholders, sponsors, and center-based early care and education (ECE) program directors pertaining to child nutrition (e.g., provision of nutritious foods, mealtime practices, CACFP administration/use) and the provision of child-care (i.e., day-to-day ECE operations and programming) during the COVID-19 pandemic.MethodsParticipants included stakeholders from 22 national and state agencies associated with the Child and Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In a study of ECE stakeholders, sponsors, and center directors, about one-third of respondents noted difficulty in finding healthy foods to purchase, 41% stopped serving family-style meals, and 20% served frozen or canned fruits and vegetables more than normal. 5 A 2021 qualitative study reported a general decline in the nutritional quality of foods served at childcare programs nationwide. 29 These findings align with our findings that nutritional BPs related to the quality of food served declined during the pandemic among Illinois ECE providers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study of ECE stakeholders, sponsors, and center directors, about one-third of respondents noted difficulty in finding healthy foods to purchase, 41% stopped serving family-style meals, and 20% served frozen or canned fruits and vegetables more than normal. 5 A 2021 qualitative study reported a general decline in the nutritional quality of foods served at childcare programs nationwide. 29 These findings align with our findings that nutritional BPs related to the quality of food served declined during the pandemic among Illinois ECE providers.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been studies of the impact of the pandemic on ECE enrollment challenges,5,25-28 program costs and responsibilities,5,25 supply chain issues,25,27 and challenges with virtual adaptations for operating a childcare facility,5,28 few studies have addressed changes in nutrition and PA-related BPs for ECE programs during the pandemic. In a study of ECE stakeholders, sponsors, and center directors, about one-third of respondents noted difficulty in finding healthy foods to purchase, 41% stopped serving family-style meals, and 20% served frozen or canned fruits and vegetables more than normal 5. A 2021 qualitative study reported a general decline in the nutritional quality of foods served at childcare programs nationwide 29.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations